Adipose tissue mitochondrial respiration and lipolysis before and after a weight loss by diet and RYGB. (4th September 2015) - Hansen, Merethe; Lund, Michael T.; Gregers, Emilie; Kraunsøe, Regitze; Van Hall, Gerrit; Helge, Jørn W.; Dela, Flemming
<x xml:space="preserve">Abstract</x> Objective To study adipose tissue mitochondrial respiration and lipolysis following a massive weight loss. Methods High resolution respirometry of adipose tissue biopsies and tracer determined whole body lipolysis. Sixteen obese patients with type 2 diabetes (T2DM) and 27 without (OB) were studied following a massive weight loss by diet and Roux‐en‐Y gastric bypass (RYGB). Results The mitochondrial respiratory rates were similar in OB and T2DM, and the mass‐specific oxygen flux increased significantly 4 and 18 months post‐surgery (P < 0.05). With normalization to mitochondrial content, no differences in oxidative capacity after RYGB were seen. The ratio between the oxidative phosphorylation system capacity (P) and the capacity of the electron transfer system (E) increased 18 months after RYGB in both groups (P < 0.05). Lipolysis per fat mass was similar in the two groups and was increased (P < 0.05) and lipid oxidation during hyperinsulinemia decreased 4 months post‐surgery. In T2DM, visceral fat mass was always higher relative to the body fat mass (%) compared to OB. Conclusions Adipose tissue mitochondrial respiratory capacity increases with RYGB. Adipocytes adapt to massive weight loss by increasing the phosphorylation system ratio (P/E), suggesting an increased ability to oxidize substrates after RYGB. Lipolysis increases in the short term post‐surgery, and insulin sensitivity for suppression of lipolysis increases with RYGB.